COMPARISON OF LAWS REGULATION OF PROFESSIONAL ORGANIZATIONS OF ADVOCATES IN INDONESIA AND MALAYSIA : PERBANDINGAN HUKUM PENGATURAN ORGANISASI PROFESI ADVOKAT DI INDONESIA DENGAN MALAYSIA - Selly, Grees (Constitutional Law Society, 2025)
Advocates are one of the main pillars in law enforcement in Indonesia. To strengthen the existence of advocates as the main pillar of law enforcement, Law No. 18 of 2003 concerning Advocates was established. The purpose of establishing the Advocates Law is to provide guarantees of professionalism, independence and independence of the profession by upholding the principles of the rule of law and the constitution. Regulating the advocate profession is very difficult. Since the Advocates Law was enacted until now, there have been frequent incidents within the advocate profession that have ended in judicial review to the Constitutional Court. The conflicts that often occur are related to the interpretation of the provisions of the article concerning advocate organizations. Initially, advocates designed advocate organizations with a single organizational system as formulated in Article 28 paragraph (1) of the Advocates Law which states that: "advocates organizations are the only free and independent advocate profession forum formed in accordance with the provisions of this law with the intent and purpose of improving the quality of the advocate profession." This article often covers between advocate organizations that adhere to a single organizational system (single bar system) with advocates who are accommodated by more than one organization (ulti bar system). The conflict between advocate organizations indirectly brings the Supreme Court Institution into a vortex of problems related to the authority to organize the swearing-in of Advocates. The Supreme Court Letter Number: 73/KMA/HK.01/IX/2015 dated September 25, 2015 has opened up an opportunity for Advocate Organizations other than PERADI to encourage the swearing-in of Prospective Advocates at the High Court in the Advocate's domicile jurisdiction. With its emergence The Supreme Court's letter adds new polemics amidst the division of the Advocates' organization which has not been managed well. Unlike Indonesia, the Advocates' Professional Organization in Malaysia is known as the Malaysian Bar (Badan Peguam Malaysia), which is a Legal Entity established based on the Advocates and Lawyers Act of 1947 and was later revoked and replaced by the Legal Profession Act 1976 or the Legal Profession Act of 1976. The organization is an Independent Lawyer organization that aims to uphold the supremacy of law and justice and protect the interests of the legal profession and the community. Every advocate and lawyer in Malaysia automatically becomes a member of the Malaysian Bar, as long as he or she has a valid Practice Certificate. In Malaysia, an Advocate's License is not based on the Court Oath Report but is sufficient with a Practice Certificate issued by the Malaysian Bar Association. PERADI, which is the sole advocate organization based on the mandate of Law No. 18 of 2003, is in fact very different from the sole advocate profession organization in Malaysia known as the Malaysian Bar Association. This article compares the regulation of the advocate profession in Indonesia which adopts a civil law system with Malaysia which adopts a common law system. The purpose of writing this article is to: first, analyze and compare the rules related to the Advocate Profession and Law Enforcement in Indonesia and Malaysia; second, analyze the regulation of the advocate profession organization in Indonesia by comparing the regulatory system in Malaysia. This normative legal research uses a statute approach and a comparative approach. Based on the results of the study, it was found that the rules related to advocates and advocate organizations have been regulated in Law No. 8 of 1981 concerning the Criminal Procedure Code, Law No. 48 of 2009, Law No. 18 of 2003 concerning Advocates and the Constitutional Court Decision Number 66/PUU-VIII/2010 dated June 27, 2011 and the Constitutional Court Decision Number 35/PUU-XVII/2018. The doctrine of comparative law can be used so that this method can improve the regulation of advocate organizations as law enforcers who provide certainty and justice to the community.